FIVE DECADES OF DECLINE FOR OLD-GROWTH INDICATOR LICHENS IN SCOTLAND. (30th May 2019) - Ellis, C. J.; Coppins, B. J.
Abstract : Systematic data collection for direct statistical analysis of biodiversity trends tends to be focused on charismatic fauna and flora such as birds or vascular plants. When subsequently applied by conservation agencies in summary metrics tracking habitat and species protection, these patterns in biodiversity loss or gain can fail to capture outcomes for groups that have a prominent importance in habitat composition, diversity and ecological function, such as algae, bryophytes, lichens and other fungi. Such species are primarily recorded on an ad hoc basis by taxonomic specialists, yielding noisy data that present problems in robustly identifying trends. This study explored the use of ad hoc field-recorded data as a potential source of biodiversity information, by comparing the pattern of recording for carefully selected indicator species with those for benchmark or control species as a proxy for recording effort. Focusing on Scotland's internationally important epiphytic lichens, and especially 'old-growth' indicator species, British Lichen Society data revealed a decline in the extent of these species in Scotland, relative to recording effort, over a period of five decades. A recent slowing in the rate of decline is observed but remains to be confirmed. The long-term decline is consistent with the effect of land use intensification, resulting in small and isolated populations that are vulnerable to extinction debt. We caution that remedial protection and monitoring for such populations remains vital as a complement to Scotland's larger scale ambition for increased woodland extent and connectivity.